FEMINIST NONCANONICAL RE-READING OF PLATO’S PHILOSOPHY (Annual of the Faculty of Philosophy in Skopje, 2013)
Rethinking the questions and methods of the history of philosophy, understanding its meaning as part of the search for the truth and solutions of our present problems and dilemmas, feminist history of philosophy is opening new directions in reading the philosophical texts. Essentially inspired by the postmodern and psychoanalytic discourse, Iragaray and Cavarero are rereading the Platonic text, through unveiling the sedimented meanings of the dominant misogynistic approach. Reading the allegory of the cave as hystera, re-legitimating the bodily love in Diotima’s speech in (iSymposium”, “stealing” the Plato ’s feminine figures from their patriarchal discourse in which they were trapped for centuries to point out the sexual difference and the primacy of the birth, feminist interpretations are stressing out the importance of the “unthought” that lays under the surface of Plato ’s ideas. Whether feminist interpretation is making the same mistake with re-canonizing the interpretative feminist principles, is the question that this article is trying to pose.
Keywords: PLATO; FEMINISM; HISTORY OF PHILOSOPHY; CANON; IRIGARAY; CAVARERO